Analyses of chemical composition and gastroprotective and antinociceptive properties of Eugenia involucrate DC. leaves - Giovana Vechi, Adriana Campos, Roseane Leandra da Rosa, Karla Capistrano, Tailyn Zermiani, Fátima de Campos Buzzi, Sérgio Faloni de Andrade, Valdir Cechinel Filho (Journal of Applied Pharmaceutical Science, 2018)
Eugenia genus has shown relevant therapeutic results as a medicinal plant, and that is why this study aimed to know the chemical composition of E. involucrata leaves and its gastroprotective and antinociceptive potential. The leaves were collected at two moments, January and July of 2014. Leaves were macerated in methanol, resulting in Crude Methanol Extracts (CME), denominated CME-jan and CME-jul. The extracts were partitioned with chloroform and ethyl acetate. Phytochemical analysis was performed by conventional chromatographic techniques and the isolated substances were analyzed by usual spectrometric techniques. The major substance isolated from the ethyl acetate fraction was (-)-catechin and phytol from the chloroform fraction. The gastroprotective evaluation was performed by the ulcer model induced by ethanol, and the extract reduced significantly the total damaged area and the area of injury relative to the treatments with doses of 125 and 250 mg/kg, but the 125 mg/kg dose was more effective. The antinociceptive activity was evaluated by the writhing test induced by acetic acid. Extract and fractions reduced the nociception (26.5 to 64.4% at 10 mg/kg). Chloroform fraction collected in July exhibited more pronounced effect (DI50 of 2.33 mg/kg).
Keywords: Eugenia involucrate, antinociceptive activity, catechin, phytol, gastroprotection.